Efficacy of the spatial repellent SC Johnson Mosquito Shield™ against anophelines in free-flight chambers, semi-field systems, experimental huts, and in-home tests - Swai, Johnson K.; Ntabaliba, Watson S.; Ngonyani, Hassan A.; Makungwa, Noely O.; Mseka, Antony P.; Ngoyani, Saphina H.; Kibwengo, Ibrahim S.; Mpelepele, Ahmadi B.; Moore, Jason D.; Chura, Madeleine R.; Mascari, Thomas M.; Moore, Sarah J. (Frontiers in Malaria, 2025)
BackgroundEvaluation of vector control tools follows a phased approach, progressing from laboratory studies to semi-field trials in experimental huts, and finally to small-scale (in-home test) and large-scale (randomized control trials) field evaluations under user conditions. Method selection depends on the specific data objectives.MethodsWe assessed the entomological efficacy of the transfluthrin-based spatial repellent product SC Johnson Mosquito Shield™ in free-flight chambers, semi-field and field experimental hut trials, and an in-home test against Afrotropical malaria vectors. We focused on efficacy endpoints and mosquito collection methods to inform evidence-based evaluation of spatial repellents.ResultsMosquito Shield reduced number of mosquitoes blood-feeding and landing, and also induced mortality, exophily, and deterrence at different magnitudes across the testing methods. However, not all endpoints were measurable with every method. Landing reductions were measured using human landing catches and remained similar in magnitude across experimental hut tests in the semi-field (71%) and field (70%), as well as in-home tests (66%), but were higher in the free-flight chambers (96%) using a susceptible mosquito strain. Other endpoints (mortality, and exophily) generally showed higher estimates in controlled environments with lab-reared mosquitoes, compared to ambient conditions with wild, free-flying mosquitoes.ConclusionThis study supports the use of multiple test methods to generate entomological efficacy data required for country registrations, WHO prequalification dossiers, and post-deployment monitoring. The findings highlight the strengths and limitations of free-flight chambers, semi-field systems, experimental huts, and in-home tests in generating efficacy data for new spatial repellent products. These results support integration of Mosquito Shield into malaria vector control programs pending further operational evaluation. Mosquito landing reduction estimated via human landing catches is a reliable metric for monitoring spatial repellent product longevity across efficacy testing methods. The efficacy gradient between controlled and ambient conditions highlights the importance of testing under realistic settings before public health deployment.